Human Virtues And Social Responsibility Of An Entrepreneur: Social-Philosophical Analysis (Eurasian Journal of Humanities and Social Sciences, 2026)
This article analyzes the entrepreneur’s human qualities and social responsibility from a socio-philosophical perspective. The relevance of the study lies in the fact that in the modern market economy the entrepreneur can no longer be understood merely as a profit-seeking economic agent, but must also be viewed as an active subject who shapes social trust, moral legitimacy, stakeholder relations, and collective well-being. The aim of the article is to conceptualize the entrepreneur’s human qualities and social responsibility not simply as matters of private morality, but as an integrated socio-philosophical construct formed at the intersection of economic activity, institutional norms, stakeholder relations, social capital, and cultural values. The study employs axiological, hermeneutic, comparative-analytical, institutional, and stakeholder approaches. The literature review demonstrates that recent research on entrepreneurship ethics has expanded rapidly, that entrepreneurs’ personal values influence corporate social responsibility orientations, and that trustworthiness stands at the ethical core of organization–stakeholder relations. As a result, the article proposes a six-component model of entrepreneurial human qualities and social responsibility: integrity, justice, empathy, trustworthiness, self-restraint, and a commitment to social usefulness. The study concludes that human qualities in entrepreneurship are not decorative additions to business, but the normative foundation of its legitimacy, sustainability, and public acceptability